Killer whale nuclear genome and mtDNA reveal widespread population bottleneck during the last glacial maximum - Andre Moura; Charlene Janse van Rensburg; Marilyn E. Dahlheim; A. Rus Hoelzel; Malgorzata Pilot; Arman Tehrani; Peter B. Best; Meredith Thornton; Stephanie Plon; P. J. Nico de Bruyn; Kim C. Worley; Richard A. Gibbs (2014)
Ecosystem function and resilience is determined by the interactions and independent contributions of individual species. Apex predators play a disproportionately determinant role through their influence and dependence on the dynamics of prey species. Their demographic fluctuations are thus likely to reflect changes in their respective ecological communities and habitat. Here we investigate the historical population dynamics of the killer whale based on draft nuclear genome data for the Northern Hemisphere and mtDNA data worldwide. We infer a relatively stable population size throughout most of the Pleistocene, followed by an order of magnitude decline and bottleneck during the Weichselian glacial period. Global mtDNA data indicates that while most populations declined, at least one population retained diversity in a stable, productive ecosystem off southern Africa. We conclude that environmental changes during the last glacial period promoted the decline of a top ocean predator, that these events contributed to the pattern of diversity among extant populations, and that the relatively high diversity of a population currently in productive, stable habitat off South Africa suggests a role for ocean productivity in the widespread decline.